The Contribution of Immune Evasive Mechanisms to Parasite Persistence in Visceral Leishmaniasis - de Freitas, Elisangela Oliveira; Leoratti, Fabiana Maria de Souza; Freire-de-Lima, Célio Geraldo; Morrot, Alexandre; Feijó, Daniel Ferreira (Frontiers in Immunology, 2016)
Leishmania is a genus of protozoan parasites that give rise to a range of diseases called Leishmaniasis that affects annually an estimated 1.3 million people from 88 countries. Leishmania donovani and Leishmania (L.) infantum chagasi are responsible to cause the visceral leishmaniasis. The parasite can use assorted strategies to interfere with the host homeostasis to establish persistent infections that without treatment can be lethal. In this review, we highlight the mechanisms involved in the parasite subversion of the host protective immune response and how alterations of host tissue physiology and vascular remodelling during VL could affect the organ-specific immunity against Leishmania parasites.